Análisis de las propiedades físicas y mecánicas del hormigón elaborado con cerámicos reciclados como sustituto del agregado grueso - Hernández Ávila, Edison Eráclides (2018)
This investigation was carried out due to the large number of ceramic elements that are rejected, destroyed and transported to the authorized dumps of the Metropolitan District of Quito, in order to use it in the field of construction and reduce the adverse environmental impact; for which the adaptation of the shredded ceramic waste has been proposed as a substitute for the coarse aggregate in a concrete designed for a compressive strength of f'c: 24 MPa, and to identify the incidence that this substitution causes in the physical and mechanical properties of concrete. In total, evaluated 14 cylindrical samples of a conventional concrete with a typical design of the ACI 318 and 72 cylindrical samples for an experimental concrete with residues of ceramic material, residues that were sieved, reflecting a reduction of 10% in the resistance to compression. With respect to the modulus of elasticity in the deformation range from 2º/oo to 3 º/oo, the value of the acting force considered for the design of reinforced concrete elements exceeded 24 Mpa.